Structural, magnetic and electrical properties of Ho and Ni co-doped BiFeO3 materials - Thang, Dao Viet; Hung, Nguyen Manh; Thu, Bui Thi; Oanh, Le Thi Mai; Tu, Bui Dinh; Minh, Nguyen Van (Vietnam Journal of Science and Technology, 2020)
Pure BiFeO3 (BFO) and Bi1-xHoxFe0.97Ni0.03O3 (x = 0.00, 0.025, 0.05, 0.075, and 0.10) materials were synthesised by sol-gel method. Effects of (Ho, Ni) co-doping on structural, magnetic and electrical properties of BFO materials were investigated by different techniques as X-ray diffraction (XRD), energy dispersion X-ray (EDX), Raman scattering, magnetic hysteresis (M-H) loops, and complex impedance spectra measurement. Analysis results of XRD measurement shows that all samples crystallize in the rhombohedral structure with R3C space group. BFO in the rhombohedral structure has crystal lattice parameters a = 5.584 Å, c = 13.867 Å and average crystal size LXRD = 60 nm. The x = 0.00 sample (BFNO) has a = 5.589 Å, c = 13.875 Å and LXRD = 60 nm. However, the crystal lattice parameters a, c and average crystal size LXRD of (Ho, Ni) co-doped samples decrease when concentration of Ho increases. Results of Raman scattering spectra shows that the peaks position characteristic for Fe-O bonds of x = 0.00 sample shifts toward lower frequency compare to that of BFO. For the (Ho, Ni) co-doped samples (BHFNO), the peaks position characteristic for Bi-O convalent bonds shifts toward higher frequency when concentration of Ho increases. Which confirmed that Ho3+ and Ni2+ ions substituted into Bi-sites and Fe-sites, respectively. From data of magnetic hysteresis loops measurement indicates that all samples present weak ferromagnetic. BFO sample presents weak ferromagnetic properties with saturation magnetization Ms = 0.047 emu/g and remnant magnetization Mr = 0.008 emu/g. Ferromagnetic properties of (Ho, Ni) co-doped samples enhance compare to that of BFO. In this report, we will discuss the origin of ferromagnetism of materials.